2008
DOI: 10.1007/s10750-008-9415-z
|View full text |Cite
|
Sign up to set email alerts
|

The use of artificial spawning substrates as media to support the reproduction of Eurasian perch in Lake Piediluco

Abstract: Lake Piediluco is a naturally regulated lake used for hydroelectric purposes. Management of the lake and the eutrophic conditions of its waters have had a negative impact on fish populations, particularly that of Eurasian perch (Perca fluviatilis L.). In order to increase the natural reproduction of this species, an experimental program was undertaken from 1997 to 2003 to facilitate reproduction by providing artificial spawning substrates. In Lake Piediluco perch spawn from March to May. Egg ribbons ranged in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Due to the continuous filling of the lake the rest of the dead common reed, worm weed and trees and branches are now mostly situated in very deep water in inappropriate temperature conditions, at least at the beginning of the perch spawning period. As the presence of live submerged vegetation is less predictable in time, moreover, it is not much suitable spawning substrate for perch (Čech et al, 2009, 2010), the installation of an artificial spawning substrate Dubois et al, 1996;Nash et al, 1999;Pedicillo et al, 2008;Probst et al, 2009), preferentially in depth layers of 3-8 m, would, in the near future, be an important means of both sustaining the stock of perch, the main predatory fish in the lake, and for overall management of the lake's ichthyofauna. The results from the above mentioned attempt (artificial spawning substrate installation) on the population of perch in Chabařovice Lake would be of crucial importance for other large water bodies forming in the region of North-West Bohemia, such as the opencast mine lake Most-Ležáky (area 311 ha; filling started in 2008), Medard-Libík (area 486 ha; filling started in 2010) or Jiří-Družba (area 1322 ha; filling will start in 2036).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the continuous filling of the lake the rest of the dead common reed, worm weed and trees and branches are now mostly situated in very deep water in inappropriate temperature conditions, at least at the beginning of the perch spawning period. As the presence of live submerged vegetation is less predictable in time, moreover, it is not much suitable spawning substrate for perch (Čech et al, 2009, 2010), the installation of an artificial spawning substrate Dubois et al, 1996;Nash et al, 1999;Pedicillo et al, 2008;Probst et al, 2009), preferentially in depth layers of 3-8 m, would, in the near future, be an important means of both sustaining the stock of perch, the main predatory fish in the lake, and for overall management of the lake's ichthyofauna. The results from the above mentioned attempt (artificial spawning substrate installation) on the population of perch in Chabařovice Lake would be of crucial importance for other large water bodies forming in the region of North-West Bohemia, such as the opencast mine lake Most-Ležáky (area 311 ha; filling started in 2008), Medard-Libík (area 486 ha; filling started in 2010) or Jiří-Družba (area 1322 ha; filling will start in 2036).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the results have shown that live vegetation is not much suitable spawning substrate for perch. For that reason, installation of an artificial spawning substrate (Gillet & Dubois, 1995;Dubois et al, 1996;Nash et al, 1999;Pedicillo et al, 2008;Probst et al, 2009) would, in the near future, be an important means of both sustaining the stock of perch, the main predatory fish in the lake, and for overall management of the lake's ichthyofauna. by the Grant Agency of the Czech Republic (projects No.…”
Section: Resultsmentioning
confidence: 99%
“…Zhakov, 1964;Frank, 1967;Pivnička, 1979;Viljanen & Holopainen, 1982;Treasurer, 1983;Craig, 1987;Lang, 1987;Urho, 1996;Pedicillo et al, 2008). Although the preference for submerged vegetation sensus lato as a spawning substrate seems to be obvious in perch, most studies do not provide any evaluation of this preference (Frank, 1967;Holčík, 1969;Craig, 1987;Gillet & Dubois, 1995;Urho, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…to either control their population ("biomanipulation purposes"; Jones 1982), to more easily study its spawning biology (Zeh et al 1989;Huff et al 2004;Gillet, and Dubois 2007;Probst et al 2009) or to support the reproduction success of this species (Nash et al 1999;Pedicillo et al 2008). In Chabařovice Lake, the A.S.S.…”
Section: Discussionmentioning
confidence: 99%